Construction of a 3D mammary duct based on spatial localization of the extracellular matrix. (October 2018) - Cho, Youngkyu; Moon, Woo; Kim, Hoe; Na, Kyuhwan; Yang, Ji; Huh, Yang; Kim, Jeong; Chung, Seok; Lee, Su
Abstract Extracellular matrix (ECM)-based hydrogels can serve as scaffolds in reconstruction of physiologically relevant three-dimensional (3D) in vitro models. Biocompatible or integrated hydrogels can be used to modulate ECM properties such as stiffness and composition for studies of cell−ECM interactions and morphogenesis. To this end, we developed a new type of spatially modified collagen type 1 hydrogel by convective addition of collagen type 1 solution. The matrix displayed properties that were distinct from those of a collagen type 1 hydrogel and recapitulated the morphology and function of mammary epithelium in a 3D microfluidic platform. In this ECM, mammary epithelial cells secreted laminin and exhibited self-assembly into a basement membrane. Thus, this spatially modified ECM offers biophysical features that can facilitate the construction of mammary epithelium and, by extension, that of various other epithelial types. Additionally, our reconstructed mammary duct can be used as an in vitro model for the study of early-stage breast cancer. In this study, we present a new type of spatially modified ECM composed of type 1 collagen whose properties differ from those of a collagen matrix. Using this ECM, we developed a stable human mammary epithelium with a lumen structure that exhibited a barrier function in a microfluidic platform, produced laminin, and formed a basement membrane. This reconstructed mammary duct can serve as a model for investigating breast cancer and may be adapted to other types of epithelium for in vitro studies. Biomaterials: constructing 3D mammary ducts A biomaterial that mimics human mammary ducts has been developed by scientists in South Korea and could be used to investigate early-stage breast cancer. Hydrogels are networks of polymer molecules that have a physical texture similar to that of the extracellular matrix surrounding and supporting cells in the human body, making them ideal scaffolds for building artificial tissue. Seok Chung from Korea University in Seoul, Su Hyun Lee from the Seoul National University Hospital and their co-workers made a hydrogel with the structure of mammary ducts using collagen, and then deposited mammary epithelial cells throughout it. The hydrogel was incorporated into a microfluidic device, providing a way of introducing the various biological components found in a natural extracellular matrix into it, and thereby a method to test how these components interact with the cells.